Contraction Mapping Principle Approach to Differential Equations - Dhungana, Bishnu P. (Nepal Journal of Science and Technology, 2010)
Using an extension of the contraction mapping principle, a new approach has been proposed in proving the existence of unique solutions of some differential equations. Key words: Contraction; Existence and uniqueness; Differential equations DOI: 10.3126/njst.v10i0.2950 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 149-153